Politik Hukum Penyelesaian Pelanggaran HAM Masa Lalu: Melanggengkan Impunity - Suparman Marzuki (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research is focused on human right law to solve the violence against human right in the past. This research also will see the enforcement of human right goes on, what kind of human right law should be made, and how to prevent the violence against human right by the authority. This research conducts a political, legal, historical, and sociological approach. The result of this research concludes that the politic of human right law enforcement in the reformation era failed to solve the problems related to human right violence. The government could not be able to give punishment to the criminals and give justice to the victims. The rules made by the government were just responsive in the process but not in the substance. The Ad hoc court of human resource was not a legal way to solve the problem, but a way to enforce impunity.Key words : Legal polici, human right, impunity